COVID-19, Diffuse Anxiety, and Public (Mis)Trust in Government: Empirical Insights and Implications for Crime and Justice - Reid, Jonathan C. (Criminal justice review, 2024)
Given that trust in government is a critical feature of a well-functioning democracy, research into its determinants has long been a priority among public opinion scholars. The consensus in the literature is that short-term factors drive the ebbs and flows of public trust, and a climate of mistrust has significant consequences on the government's ability to deliver on policies and enforce the law. Despite decades of extensive research on public trust, changing circumstances related to the COVID-19 pandemic support the need to investigate the factors shaping trust in this distinct period. This article, using data from the American National Election Study, explores how economic, social, and political anxieties pervasive throughout the pandemic influence trust in the United States government. Findings from ordered logistic regression analyses indicate that public trust in government is associated with views of the government's COVID-19 response, beliefs about the state of the country and government corruption, economic anxieties, and concerns about election fraud and the status of American democracy. Findings also reveal that sentiments toward institutions—including the police and the Center for Disease Control—contribute to variability in public trust. The implications of these findings for criminal justice research and policy are also considered.